Tarekat and the Islamic Moderation Campaign on Digital Media: A Critical Study of JATMAN’s Site at Jatman.or.id Site - Khodijah, Khodijah (Religió Jurnal Studi Agama-agama, 2023)
This article discusses the activity of Jam‘iyyah Ahli al-Tarīqah al-Mu‘tabarah al-Nahdiyyah (JATMAN) in promulgating Islamic moderation on digital media. Given the swift flow of narratives of radicalism that has spread to various corners of the archipelago, an alternative contribution from the Sufi order (tarekat) is necessary regarding the scheme and model of mainstreaming Islamic moderation on the digital realm in order to deal with this problem. This research focuses on the Islamic moderation found at JATMAN’s official website, namely jatman.or.id. The research employs a qualitative approach which examines documents, manuscripts, audio-visual, and other authoritative sources. The collected data is analyzed and described descriptively and narratively. To enrich the method, Marshall McLuhan’s mass media theory is also used. This study reveals that the mainstreaming model of Islamic moderation found at jatman.or.id. is formatted in the presentation of short articles and short video recordings that emphasize the insistence of moderate Islam and its applicability with the Sufism. In addition, viewed from Marshall McLuhan’s theory it is also found that JATMAN has creatively implemented certain formula to make the dissemination of Islamic moderation more efficient and attractive using its own website, i.e. Jatman.or.id. It seems that the existence of Islamic moderation campaign of JATMAN will continue along with the existence of the Jatman.or.id to deliver messages of peaceful Islam.